MENGOPTIMALKAN PEMBELAJARAN AKUNTANSI DASAR MELALUI PEMBUATAN VIDEO EDUKATIF - Bonal, Emilie Monique; Wijoyo, Amin (Jurnal Serina Abdimas, 2024)
This activity aims to improve accounting education by introducing a video-based learning approach that emphasizes understanding the basics of accounting, specifically through the book "Introduction to Accounting Study Guide" and the "Introduction to Accounting" module. Traditional education methods at school involve face-to-face interaction with Tarumanagara University lecturers and students. However, this research presents a new approach by creating learning videos that summarize key accounting theories and practical examples. This innovative approach is designed to facilitate a deeper understanding of basic accounting concepts, while ensuring accessibility and smooth learning. The primary goal is to prepare to further their academic pursuits at an advanced level. of accounting studies. However, not only that, this approach also aims to provide additional understanding for UMKM users in running their business with a strong accounting foundation. By focusing on learning videos, it is hoped that this method can become a useful resource for students and UMKM users, providing better understanding and facilitating the application of accounting concepts in real life. This strategy aims to enhance the standard of accounting education and enhance the capability of UMKM users to efficiently handle their business finances.